Impact of Anti Retro Viral (ART) Therapy on Clinical and Laboratory Parameters: A Longitudinal Study - Gorantla, Misha; Takalkar, Anant; Kondagunta, Nagaraj (National Journal of Community Medicine, 2017)
Introduction- India is among the list of countries with highest HIV prevalence. Adequate viral suppression requires strict adherence to antiretroviral therapy (ART).Telangana ranks 7th in the prevalence of HIV in India Objectives: The research was conducted to study the prevalence poor adherence among the study group and to study the effect of poor adherence on clinical and laboratory deterioration. Methodology-This is an observational follow up (longitudinal) study done on 142 patients which includes all newly diagnosed (diagnosed on or after 1st January 2012), sero positive, adult patients, enrolled at ART centre Nalgonda and started on treatment during the months of December 2012, January 2013, February 2013, using a pre designed, pre tested questionnaire. They were visited one year after ART initiation and their clinical and laboratory parameters were studied. Results-After one year 129 patients remained, of which 49.61% patients had good adherence and 50.39% patients had poor adherence. Decrease in BMI, worsening of HIV grade, presence of opportunistic infections were significantly present among patients with poor adherence. Low CD4 count and severe anaemia were also significantly associated with poor adherence. Conclusion- There is significant worsening of clinical and laboratory parameters in patients with poor adherence.